Evaluation of an Ayurvedic polyherbal formulation (Sindhuvaradi agada) in Doxorubicin induced Cardiotoxicity- in wistar rats - Shrutika Subhash Karoshi; Kolume Dugeppa Govindappa; Kalanghot Padmanabhan Skandhan (Indian Journal of Ayurveda and Integrative Medicine KLEU, 2018)
Background: Presently cancer is second major cause of death in India. Doxorubicin, an anthracycline is frequently used to treat various human malignancies but at same time its use is warranted with irreversible cardiomyopathy. Ayurveda, ancient science of Medicine has advocated various herbal drugs for toxicological cases which include protection of Hrudaya (cardio-protective) and Sindhuvaradhi agada is one of them indicated for cobra envenomation. Objective: Study was aimed to evaluate Sindhuvaradi agada in Doxorubicin induced cardio-toxicity in Wistar rats. Methodology: Group I served as control. Cardio-toxicity was induced by Doxorubicin administration (15 mg/kg body weight for 2 weeks) in Group II. Group III was pretreated with aqueous solution of Sindhuvaradi agada (216 mg/kg body weight) for 2 weeks followed by Doxorubicin for next 2 weeks. In Group IV cardio-toxicity was produced by Doxorubicin administration for 2 weeks followed by administration of Sindhuvaradi agada in next 2 weeks. General mortality, histopathology of heart and biomarker enzymes (CPK-MB, SGOT, SGPT and Lipid Profile)was evaluated. Results: Pretreatment with Sindhuvaradi agada significantly (p<0.05) controlled myocardial damage as reflected in biomarker enzymes [CPK-MB (241.3 ± 5.25), SGOT (225.8 ± 6.63)] and also minimized the cardio myocyte damage when compared to Doxorubicin treated group [CPK-MB (258.8 ±18.33),SGOT(534 ± 102.8)].